Educação infantil: as práticas pedagógicas lúdicas de alfabetização e letramento - Asquino, Andreia Bugui (2019)
This dissertation contains considerations about literacy and your possible dialogues with the play in the early childhood education. Your content is the result of bibliographical research desenvolved by the following problematization: considering the importance of the writing in our society, how the school can by playful pedagogical practice promote the literacy with kids of four to five years old without schooling then prematurety? The research was desenvolved guided by the hypothesis of, in the school, the work with literacy in a playful perspective can be desenvolved along the early childhood education inasmuch as promote, naturally and enjoyably the familiarization with the system of alphabetical writing in the way that the children come to understand and use it with the resourcefulness along the practice of reading and writing, although even though dominate your particularities of working. The research objective demonstrate enabling the access of the children to literate culture by significant situations of reading and writing, especially strongly playful situations, awake the interest of the same in use this knowledge. Because, the process of literacy give not just in the literacy domain, but the reading of world at all, in the way that defend the literacy in this stage of desenvolviment, betwixt three to five years old, is defend the pleasure of the discoverings, the wish to know, the stimulus to curiosity and that the process of literacy explores the alphabetization, even it is a condition sine qua non for this to happen. An important result was the observation that don’t have agreement by the work with the reading and writing in the early childhood educations and too by the playful in this work. For some scholars, that would be one anticipation not properly of what need to do in the Primary School, pushing aside the interations and plays so important in this age range. This research walked on the direction of isn’t applicable in early childhood education of objective the alphabetization of the children. This, however, don’t mean the process of progressive approximation to the reading and writing can’t be initiated in this moment of the children. To this progressive approximation is named here, of literacy. Therefor more if this progressive aproximation it’s envolved in the typical playfulness of this moment of the human life.